The poetry of space in the contemporary Algerian Triple Ahlam Mostaganemi as a model (مجلة إحالات, 2026)
The poetic language came as a reaction to the normative language of utilitarianism with strictboundaries and laws. The modern fiction is based on a revision of the linguistic system of writingthrough the creation of experimental creative spaces that were never consumed. , While the poeticlanguage gives us a wide range of semantic options, and this makes the text open to variousinterpretations that nourish and develop the text, and the place is only an essential element in thisdiscourse which is not founded without it. This is why the novelist tried to adapt it aesthetically tokeep up with the expectations of the sinful reader